Copper-catalyzed domino cyclization of anilines and cyclobutanone oxime: a scalable and versatile route to spirotetrahydroquinoline derivatives - Jiang, Qingqing; Lei, Xinyi; Gao, Pan; Yuan, Yu (Beilstein Journal of Organic Chemistry, 2025)
In this study, we report the copper-catalyzed synthesis of tetrahydroquinoline derivatives via a domino reaction of aniline with cyclobutanone oxime. This method demonstrates a selective approach for generating bioactive tetrahydroquinoline scaffolds, which have broad applications in pharmaceutical chemistry. The reaction conditions were optimized for the effective formation of tetrahydroquinoline derivatives with varying substituents, showing high yields under mild conditions. Mechanistic studies suggest a catalytic cycle involving nucleophilic attack by the aniline on the cyclobutanone oxime, followed by cyclization to form the desired product.
Keywords: copper catalysis; cyclobutane-fused tetrahydroquinolines; domino cyclization reaction; green synthesis